Role of Indian ocean temperatures on droughts over Andhra Pradesh (MAUSAM, 2014)
Analysis of drought over a smaller scale region is requirement of many users, mainly planners. In the present study an attempt has been made to see the impact of Indian Ocean temperatures on the droughts over Andhra Pradesh state by considering correlation between sea surface temperature (SST) anomalies over Bay of Bengal during different months and area affected by drought over Andhra Pradesh state during the period 1950 - 2000. The study would be useful in the early warning of drought over Andhra Pradesh by monitoring of sea surface temperatures over Bay of Bengal in different grids and would be beneficial for planners.